Analisis Komparatif Indikator Penerapan Utang Luar Negeri Indonesia Ditinjau Dari Perspektif Ekonomi Islam - Subagiyo, Rokhmat; Budiman, Ahmad (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
Efforts made by the Indonesian government to meet the budget deficit by issuing stimulus policy packages from within the country and abroad. An overseas stimulus package is financing through foreign debt. Indonesia has been practicing foreign debt since before the pre-independence period, the Soekarno government regime, Suharto until the Jokowi regime. The amount of foreign debt until October 2018, USD 310.839 billion. If the state does not have the ability to repay debt, the country's economy will be disrupted. The amount of installments on loan principal and interest has an impact on the burden of the state budget, which will be borne by the community through tax collection. This study aims to compare indicators of the application of foreign debt based on Islamic economic perspectives and the results of field research. This study uses a type of qualitative approach to explain the phenomena that occur. The results of the study show that there are deviations between indicators of foreign debt based on economic perspectives and field research.